2013
DOI: 10.5152/jaem.2013.77699
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Suicide Attempts to the Emergency Department: Clinical Features of Early and Late Adolescents

Abstract: Objective: The purpose of this study was to compare the demographic and clinical features of early and late adolescents attempted suicide. Material and Methods: A cross-sectional study was conducted to examine the clinical characteristics of adolescents who attempted suicide and presented to our Emergency Department (ED) from January 2009 to December 2011. Patients were divided into two groups; Group 1 consisted of early adolescents (10-14 years) and Group 2 consisted of late adolescents (15-18 years). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Participants reported that poisoning was the most common method used by people who self-harm. Previous studies also indicated that medications (benzodiazepines), cleaning products (bleach/bathroom cleaner), rat poison, and organophosphorus compounds (pesticides) are commonly used poisons in self-harm in Pakistan (26,27).…”
Section: Comparison With Previous Literaturementioning
confidence: 99%
“…Participants reported that poisoning was the most common method used by people who self-harm. Previous studies also indicated that medications (benzodiazepines), cleaning products (bleach/bathroom cleaner), rat poison, and organophosphorus compounds (pesticides) are commonly used poisons in self-harm in Pakistan (26,27).…”
Section: Comparison With Previous Literaturementioning
confidence: 99%